Perspectives on Assembling Coronavirus Spikes on Fiber Optics to Reveal Broadly Recognizing Antibodies and Generate a Universal Coronavirus Detector - Sypabekova, Marzhan; Tosi, Daniele; Vangelista, Luca (Frontiers in Bioengineering and Biotechnology, 2021)
In time of COVID-19 biological detection technologies are of crucial relevance. We propose here the use of state of the art optical fiber biosensors to address two aspects of the fight against SARS-CoV-2 and other pandemic human coronaviruses (HCoVs). Fiber optic biosensors functionalized with HCoV spikes could be used to discover broadly neutralizing antibodies (bnAbs) effective against known HCoVs (SARS-CoV, MERS-CoV and SARS-CoV-2) and likely future ones. In turn, identified bnAbs, once immobilized onto fiber optic biosensors, should be capable to detect HCoVs as diagnostic and environmental sensing devices. The therapeutic and preventative value of bnAbs is immense as they can be used for passive immunization and for the educated development of a universal vaccine (active immunization). Hence, HCoV bnAbs represent an extremely important resource for future preparedness against coronavirus-borne pandemics. Furthermore, the assembly of bnAb-based biosensors constitutes an innovative approach to counteract public health threats, as it bears diagnostic competence additional to environmental detection of a range of pandemic strains. This concept can be extended to different pandemic viruses, as well as bio-warfare threats that entail existing, emerging and extinct viruses (e.g., the smallpox-causing Variola virus). We report here the forefront fiber optic biosensor technology that could be implemented to achieve these aims.